2021
DOI: 10.1007/s12602-021-09757-9
|View full text |Cite
|
Sign up to set email alerts
|

Anticandidal Activity of Omiganan and Its Retro Analog Alone and in Combination with Fluconazole

Abstract: Vulvovaginal candidiasis (VVC) is a vaginal infection that manifests itself as several symptoms which can lead to various life-threatening complications. The majority of VVC is caused by Candida albicans strains, and it is estimated that approximately 75% of women worldwide would suffer from this condition at least once during their lifetime. Surprisingly, the detailed pathomechanism of yeast-like fungi invasions in vagina is not yet fully understood. However, the ability to form biofilm on vaginal mucosa is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…For this reason, it is necessary to search for alternative methods of treating fungal infections based on antimicotics that effectively eradicate this structure. Antimicrobial peptides (AMPs), including Omiganan, might meet this criterion, as promising activity has already been described [ 38 ]. In the case of VVC, the MIC results obtained in this study show that fluconazole is highly active against planktonic forms of Candida .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, it is necessary to search for alternative methods of treating fungal infections based on antimicotics that effectively eradicate this structure. Antimicrobial peptides (AMPs), including Omiganan, might meet this criterion, as promising activity has already been described [ 38 ]. In the case of VVC, the MIC results obtained in this study show that fluconazole is highly active against planktonic forms of Candida .…”
Section: Discussionmentioning
confidence: 99%
“…Although, initially, in our previous report for three strains of Candida spp., the FIC determination indicated an antagonism between Omiganan and fluconazole. However, in the course of our studies on a larger group of strains, we found an additive and/or synergistic effect [ 38 ]. In both the vaginal and blood-derived strains, addition was the most common effect, affecting the majority of C. albicans isolates (6/8 with VVC and 5/6 with BSI) and 100% of the strains from the NCAC group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In effect, the composition of the cell membrane changes; it lique es and increases the permeability for K + and ATP causing a fungistatic effect 53 . On the other hand, the interaction of uconazole with the cell membrane may enhance its permeabilization by various AMPs, including lipopeptides, and enhance their fungicidal activity 51,54,55 . Other mechanisms that may be responsible for the synergistic effect of combining triazoles with compounds with a different mechanism of action include sequential inhibition of different stages in the mutual biochemical pathway or simultaneous interaction with the Candida cell wall and/or membrane 51 .…”
Section: Discussionmentioning
confidence: 99%